La universidad de la Sudamérica hispanoparlante pierde terreno: un análisis comparado con Oriente Próximo en investigación e innovación - Cisternas Irarrázabal, César (2023)
Hispanic South America and the Near East are considered peripheral regions in the global scientific system due to the size of their scientific and technological production. However, their higher education systems have shown significant growth over the last few decades. This article compares the evolution of the national higher education systems in research and innovation across all scientific disciplines in both regions. The exercise considers indicators associated with research production, scientific impact, and innovation. The results indicate that, despite their limitations, the Near East countries have increased their scientific output, extended their international collaboration networks, and improved technology transfer from universities to enterprises. In contrast, the scientific and innovation activities of countries in Hispanic South America have stagnated.